Expanding Global Rehabilitation Services through International Academic-Community Partnerships - Rawan Alheresh; Peter S. Cahn (Ubiquity Press, 2020)
Background: More than one billion people worldwide live with a disability, yet rehabilitation professionals are scarce in low- and middle-income countries. Attempts to expand access to rehabilitation services have encountered barriers on multiple levels: limited resources on the systemic level, hierarchies on the professional level, and cultural stigma on the community level. Objectives: We sought to determine if an academic-community partnership could overcome multiple levels of barriers to expand services for people with disabilities. Methods: Toward an All-Inclusive Jordan incorporates community-based rehabilitation with prelicensure health professions education to address the three primary levels of barriers to rehabilitation services in low- and middle-income countries. The yearlong curriculum includes formal training, research, and advocacy with graduate students from the United States and health professions students and community members in Palestinian refugee camps near Amman, Jordan. Findings: After two cycles of the program, 14 Jordanian volunteers have partnered with 20 graduate students from the United States. They have delivered over 300 direct rehabilitation sessions, conducted ten workshops with mothers of children with disabilities, and trained 12 community-based rehabilitation workers in the refugee camps. Conclusions: The academic-community partnership model builds on the evidence base for the success of community-based rehabilitation services in low- and middle-income countries. Its components address barriers on multiple levels to create a sustainable expansion of services to people with disabilities.